Suggestions to Prevent Unbalanced Biding Due to Quantity Error in Retrofit Constructions - Topuz, Suat; Bettemir, Önder Halis (Fırat University, 2024)
Following the devastating February 6 Kahramanmaraş earthquakes, tens of thousands of moderately damaged buildings were retrofitted and slightly damaged buildings were repaired. Since the retrofit and repair process is carried out by the inexperienced apartment managers on tender and contract management, they may be ineffective against unbalanced offers which may be submitted by experienced contractors. Moreover, contractors can have scope change requests accepted by the job owners and contract price can increase tremendously by abusing the high level of anxiety and fear in the people of the region after the earthquake. In this study, revised price practices that can prevent contractors from gaining excessive profits due to possible quantity increases based on unbalanced bids in retrofit constructions are proposed and the results are evaluated. The effectiveness of the revised unit price formula in the annexes of the public procurement law on the unbalanced bid and its application after a 0% to 20% work increase were examined. Furthermore, in order to achieve faster price decreases, the revised unit price formula has been modified by the power of the rate of increment. The application of the modified revised price formula is examined from 0% to 20% quantity increase. It is aimed to make the quantity increase of the work items unattractive by reducing the profit of the contractor who submitted an unbalanced bid. However, it is also aimed to protect contractors who submit balanced bids and prevent a rapidly falling unit prices which may cause heavy loss. According to the findings obtained in the case study, implementation of the modified revised unit price formula after the 10% work increase prevents the excessive profits of the contractor who prepares an unbalanced bid, while allowing a reasonable profit for the contractor who submits a balanced bid. In this study, it is aimed to ensure that the retrofit works are carried out fairly and safely by proposing a fair revised price application that is easy to implement and respects the rights of the parties. In this way, the job increase will not be attractive to contractors who submit unbalanced bids, and since job increases will not occur except for the necessary cases. Consequently, retrofit constructions will be carried out in a way that will not excessively affect the financial health of homeowners whose financial situation is weakened after the earthquake.

Yıkıcı 6 Şubat Kahramanmaraş depremlerinin ardından on binlerce orta hasarlı binanın güçlendirilmesi ve az hasarlı binaların tamiratı gerçekleştirilmektedir. Güçlendirme ve onarım süreci ihale ve sözleşme üzerine deneyimsiz apartman yöneticileri tarafından yürütüldüğü için deneyimli yükleniciler tarafından sunulabilecek dengesiz tekliflere karşı etkisiz kalınabilmektedir. Ayrıca deprem sonrası bölge halkında oluşan yüksek düzeydeki endişe ve korku nedeniyle yüklenicilerin iş artışı talepleri işveren tarafından kabul edilerek sözleşme bedelinin çok üzerinde iş artışları görülebilmektedir. Bu çalışmada güçlendirme işlerinde dengesiz teklife dayalı olası iş artışlarından dolayı yüklenicilerin haksız kazanç elde etmelerinin önüne geçebilecek revize fiyat uygulamaları önerilmiş ve sonuçları değerlendirilmiştir. Kamu ihale kanunu eklerinde yer alan revize birim fiyat formülünün dengesiz teklif üzerindeki etkinliği %0 ile %20 iş artışından sonra uygulanma durumu incelenmiştir. Buna ek olarak daha hızlı fiyat eksiltmesi sağlayabilmek için artış oranının üssü alınarak revize birim fiyat formülü modifiye edilmiştir. Modifiye revize fiyat formülünün %0 ile %20 iş artışından sonra uygulanması incelenmiş ve dengesiz teklif sunan yüklenicinin iş artışından dolayı elde edeceği kârı azaltarak iş artışının cazip olmaması amaçlanmıştır. Bununla beraber dengeli teklif veren yüklenicilerin hızlı düşen birim fiyat uygulamasından mağdur olmayacak düzeyde revize birim fiyat uygulanması önerilmektedir. Vaka analizi çalışmasında elde edilen bulgulara göre modifiye revize birim fiyat formülünün %10 iş artışından sonra uygulanmasının dengesiz teklif sunan yüklenicinin aşırı kâr etmesini önlerken dengeli teklif sunan yüklenicinin makul kâr elde edebilmesine olanak verdiği belirlenmiştir. Bu çalışmada uygulaması kolay ve tarafların haklarını gözeten adaletli bir revize fiyat uygulaması önerilerek güçlendirme işlerinin adil ve güvenli biçimde gerçekleştirilmesinin sağlanması amaçlanmıştır. Bu sayede dengesiz teklif sunan yükleniciler için iş artışı cazip olmayacak ve iş artışları gerekli haller dışında ortaya çıkmayacağı için deprem sonrası maddi durumu zayıflayan konut sahiplerinin finansal sağlıklarını aşırı etkilemeyecek biçimde güçlendirme işleri gerçekleştirilebilecektir.
Güçlendirme İşlerinde Miktar Hatasına Bağlı Dengesiz Teklifin Önlenmesi için Öneriler
Keywords: Building Construction Management and Project Planning; Yapı İnşaat Yönetimi ve Proje Planlaması